2013
DOI: 10.1128/cvi.00594-12
|View full text |Cite
|
Sign up to set email alerts
|

Nematode Asparaginyl-tRNA Synthetase Resolves Intestinal Inflammation in Mice with T-Cell Transfer Colitis

Abstract: The therapeutic effects of a controlled parasitic nematode infection on the course of inflammatory bowel disease (IBD) have been demonstrated in both animal and human models. However, the inability of individual well-characterized nematode proteins to recreate these beneficial effects has limited the application of component immunotherapy to human disease. The nematodes that cause chronic human lymphatic filariasis, Brugia malayi and Wuchereria bancrofti, are among the parasites that induce immune suppression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…In addition, some of these functions are extracellular and are enabled by the capacity of at least some aaRSs to be secreted, as evidenced by their detection in human and mouse sera (16, 17, 44 -47). With this in mind, there are suggestions of immunomodulation-related functions, such that aaRSs fragments have activities that can act to resolve inflammation (48,49). Thus, in light of the many examples of non-catalytic fragments of aaRSs having extracellular functions and given the data presented here showing the reactivity of SVs of HisRS for anti-Jo-1 Abs, the up-regulation of at least one of them in a patient population, and their secretion from cultured cells, we propose that these SVs deserve further investigations related to muscle health and the etiology of inflammatory muscle diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of these functions are extracellular and are enabled by the capacity of at least some aaRSs to be secreted, as evidenced by their detection in human and mouse sera (16, 17, 44 -47). With this in mind, there are suggestions of immunomodulation-related functions, such that aaRSs fragments have activities that can act to resolve inflammation (48,49). Thus, in light of the many examples of non-catalytic fragments of aaRSs having extracellular functions and given the data presented here showing the reactivity of SVs of HisRS for anti-Jo-1 Abs, the up-regulation of at least one of them in a patient population, and their secretion from cultured cells, we propose that these SVs deserve further investigations related to muscle health and the etiology of inflammatory muscle diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, PfTyrRS bound to host macrophages via its ELR peptide motif and then was internalized, resulting in increased secretion of the inflammatory cytokines TNF-ɑ and IL-6, as well as overexpression of endothelial receptors intercellular adhesion molecule-1 and vascular cell adhesion molecule-1. Furthermore, Brugia malayi asparaginyl-tRNA synthetase (BmAsnRS) has also been shown to be closely related to the host immune and inflammatory responses [21][22][23] . Kron et al 24 demonstrated that BmAsnRS activated IL-8 receptors by extracellular domains that differed from those used by IL-8, providing a basis for elucidating the molecular mechanism by which parasite ARSs participated in immune regulation.…”
Section: Pathogen Arss In Immune Responses and Antiinfective Therapiesmentioning
confidence: 99%
“…Of note, murine Jo-1 induced autoreactive B and T cells targeting its own epitopes, and the epitope spreading occurred uniformly 8 weeks after the single immunization, suggesting that autoantibody Jo-1 was able to drive a sustained immune response. When PBMCs and bronchoalveolar lavage fluid (BALF) cells from ASSD patients were stimulated with HisRS or a HisRS-derived peptide (HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] ), the expression of CD40L in CD4 + T cells from the corresponding compartments was upregulated 78 . Compared with PBMCs, BALF CD4 + T cells showed a remarkable Th1 phenotype after stimulation, such as the production of more IFN-γ and IL-2, indicating the presence of HisRS-specific CD4 + T cells in the blood and lung of patients with ASSD.…”
Section: Arss and Autoimmune Diseasesmentioning
confidence: 99%
“…Their mode of communication with host immunity could be different. For example, the filaria Brugia malayi resides in lymphatics and releases copious amounts of asparaginyl-tRNA synthetase, which can block IL8 signaling in human and murine leukocytes and can suppress murine T cell transfer colitis (57). …”
Section: Mechanisms Of Regulationmentioning
confidence: 99%